Altered vaccine‐induced immunity in children with Dravet syndrome. (7th March 2018) - Auvin, Stéphane; Jeljeli, Mohamed; Desnous, Béatrice; Soussi‐Yanicostas, Nadia; Dournaud, Pascal; Sterkers, Ghislaine
Summary: Dravet syndrome (DS) is a refractory epileptic syndrome. Vaccination is the trigger of the first seizure in about 50% of cases. Fever remains a trigger of seizures during the course of the disease. We compared ex vivo cytokine responses to a combined aluminium‐adjuvanted vaccine of children with DS to sex‐ and age‐matched heathy children. Using ex vivo cytokine responses of peripheral‐blood mononuclear cells and monocytes, we found that vaccine responsiveness is biased toward a proinflammatory profile in DS with a M1 phenotype of monocytes. We provide new insight into immune mechanisms associated with DS that might guide research for the development of new immunotherapeutic agents in this epilepsy syndrome.